Population dynamics and soil nutrient characteristics of the endangered Annamocarya sinensis in Yunnan, China - Shengjie Sun; Jiaole Liu; Xiaodong Wu; Guihua Zhang; Dan Zong; Dan Li (BMC Plant Biology)
Abstract Annamocarya sinensis is an endangered plant species with an extremely small population. This study focuses on the only two known wild populations of A. sinensis in Yunnan Province, China. Conventional population ecology survey methods were employed to describe the population structure characteristics and to predict the future population size. Subsequently, ten soil physicochemical factors were measured, followed by soil nutrient ratings, analysis of variance, correlation analyses, and exploration of C:N:P stoichiometry and its drivers. The results indicate that A. sinensis populations exhibited a general trend of decline, demonstrated high sensitivity to external disturbances. The population survival curve conforms to Deevey-III type. The high mortality rate of juvenile individuals cannot be compensated by natural regeneration. Soil analysis indicates that the Malipo region has relatively fertile soil, whereas the Funing region has poorer soil quality. Notably, both regions exhibit potassium deficiency. Stoichiometric analysis of the soil indicated an excess of nitrogen and a deficiency of phosphorus in the Malipo region, while the Funing region is characterized by low soil organic matter content. Furthermore, soil correlation analysis demonstrated that the interrelationships among soil properties were significantly stronger in the Malipo region compared to the Funing region. Given the imminent risk of extinction for the wild population of A. sinensis in Yunnan Province, we highlight the urgent need for enhanced conservation measures, particularly in the Funing region. Based on the current conditions of the A. sinensis populations, in situ conservation, germplasm preservation, and artificial cultivation to ensure the sustainable management and recovery of A. sinensis populations.